Kidney stones recurrence and regrowth after extracorporeal shock wave lithotripsy and percutaneous nephrolithotomy - Wilaiwan Chongruksut (2018)
Objective: To estimate and compare the incidence rate of kidney stone recurrence and regrowth after ESWL with PCNL at one, two, and three years. Material and Method: A retrospective cohort study was performed. The study recruited patients aged more than 18 years, diagnosed with kidney stones and treated by ESWL or PCNL between January 2006 and August 2010 at the urological unit of a university hospital located in the northern part of Thailand. Data were retrieved from medical records and analyzed using exact probability test or student's t-test. Poisson regression was used to compare the recurrence rate and the regrowth rate between ESWL and PCNL. Results: During three years of follow-up, the overall stones recurrence and regrowth were 15.5% and 25.1% in ESWL group and 12.6% and 16% in PCNL group, repectively. At one, two and three years after treatment, stones recurrence rate in the ESWL group were 13.1, 7.5 and 7.3 per 1,000 patient-months while in the PCNL group were 11.3, 6.1 and 5.4 per 1,000 patient-months. After ESWL stones regrowth rates were 29.1, 12.3 and 11.9 per 1,000 patient-months, whereas after PCNL were 11.3, 6.9 and 6.9 per 1,000 patient-months, respectively. In comparison to PCNL, the relative recurrence rate after ESWL presented as incidence rate ratio (IRR) were 1.1 (95% CI; 0.4-3.2, p = 0.762), 1.2 (95% CI; 0.6-2.6, p = 0.517) and 1.4 (95% CI; 0.8-2.5, p = 0.271) at 1, 2 and 3 years, respectively. For regrowth, the IRRs were 2.6 (95% CI; 1.1-6.5, p = 0.012), 1.8 (95% CI; 0.9-3.4, p = 0.048), and 1.7(95%CI; 1.1-2.9, p = 0.017) at 1, 2 and 3 years, respectively. Conclusion: Patients after ESWL had a higher trend of recurrent rates and statistically significant higher regrowth rates, in comparison with those after PCNL.